Implementing integrated river basin management in the Red River Basin, Vietnam: a solution looking for a problem? - Molle, Francois; Hoanh, Chu Thai (IWA Publishing, 2011)
Several water policy principles considered to be modern and internationally sanctioned have recently been adopted by Vietnam. This article focuses on the establishment of the Red River Basin Organization but expands its analysis to the wider transformations of the water sector that impinge on the formation and effectiveness of this organization. It shows that the promotion of integrated water resource management icons such as river basin organizations (RBOs) by donors has been quite disconnected from existing institutional frameworks. If policy reforms promoted by donors and development banks have triggered changes, these changes may have come not as a result of the reforms themselves but, rather, due to the institutional confusion they have created when confronted with the emergence of the Ministry of Natural Resources and Environment (MoNRE). For the MoNRE, the river basin scale became crucial for grounding its legitimacy and asserting its role among the established layers of the administration, while for the Ministry of Agriculture and Rural Development, RBOs became a focal point where power over financial resources and political power might potentially be relocated at its expense. Institutional change is shown to result from the interaction between endogenous processes and external pressures, in ways that are hard to predict.